A comparative study between the Perlis and the Kelantan dialect in Malaysia at the phonetic level - Ali, Asem Shehadeh Saleh; Alqudah, Mohammad Ahmad; Zainol, Tasneem (ISRG Publishers, 2024)
Language and dialect persist as separate concepts imply that linguists can make tidy distinctions for speech varieties worldwide. The study aims to compare Perlis and Kelantan dialects in Phonological level, it compares the differences and similarities between both dialects. The study found that the Perlis and Kelantan dialects display unique phonetic characteristics shaped by distinct cultural and historical influences. Their differences in vowel and consonant perception reflect the rich linguistic diversity of Malaysia. The differences, rather than hindering communication, enrich the cultural fabric of the nation and add depth to the study of Malaysian linguistics. This comparative study showed that although they have some similarities, the Perlis and Kelantan dialects are distinct in their phonetic systems, with each contributing to Malaysia's rich linguistic diversity. Understanding these differences can help promote stronger and more accurate.